Alveolar Soft Tissue Sarcoma: Correlation of MRI Features With Histological Grading and Patient Prognosis - Yuan, Junhui; Xie, Deshun; Fang, Shaobo; Meng, Fan; Shan, Dongqiu; Wang, Yuanyuan; Du, Xinhui; Xu, Chunmiao; Zhang, Renzhi; Chen, Xuejun (Journal of magnetic resonance imaging, 2025)
Background Alveolar Soft Part Sarcoma (ASPS) is a rare, aggressive cancer whose diagnosis and treatment depend on histological grading. However, tumor variability can lead to underestimation, affecting treatment, and patient survival. Objective To evaluate MRI features associated with Grade III ASPS and to determine the relationship between MRI features and patient prognosis. Study Type Retrospective analysis. Subjects Sixty‐seven patients with ASPS were included with 37 males and 30 females (M/F = 1.23) follow‐up and survival analysis on 50 patients. Field Strength/Sequence A 3.0 T, T1WI‐FSE, T2WI‐FSE, DWI‐EPI, DCE‐MRI (gradient echo). Assessment MRI features (margin, peritumoral oedema, peritumoral enhancement, necrosis, vascular flow void signal, heterogeneous signal intensity [SI] at T1WI and T2WI, ADCmean, time‐intensity curve [TIC] type, distant metastasis, and bone invasion) and histological grading were independently evaluated by three radiologists and two pathologists, with Grade III considered high‐grade. Statistical Tests The chi‐square or Fisher's exact test was used to assess the correlation between MRI features and histological grading. Multivariable binary logistic regression identified independent factors associated with high‐grade tumors. The Kaplan–Meier method and Cox proportional hazards model were used to calculate hazard ratios for MRI features. Results Tumor necrosis, heterogeneous SI at T2WI ≥50%, and ADCmean were associated with high‐grade ASPS. Tumor necrosis was an independent factors associated with local relapse‐free survival (odds ratio [OR], 3.88). TIC type was associated with 5‐year survival rate (OR, 2.80) and local relapse‐free survival (OR, 2.69). Heterogeneous SI at T2WI ≥50% was associated with 5‐year survival (OR, 4.00), local relapse‐free survival (OR, 5.58), and local relapse‐free survival (OR, 4.84). Data Conclusion MRI features including tumor necrosis, heterogeneity of SI at T2WI, ADCmean, and TIC type aid in assessing ASPS grading and prognosis. Evidence Level 4 Technical Efficacy Stage 5